ISLAMIC EDUCATION IN THE ERA OF GLOBALIZATION AND MODERNIZATION - Sulkifli; Ondeng, Syarifuddin (International Journal of Multidisciplinary Reseach, 2025)
Islamic education faces complex challenges in the era of globalization and modernization, characterized by advances in information technology, sociocultural transformation, and shifts in life values. This study aims to identify the challenges facing Islamic education, analyze its fundamental characteristics, and formulate comprehensive development strategies. Using a qualitative method with library research, this study analyzes various literature related to Islamic education, globalization, and modernization through content analysis techniques. The findings reveal that Islamic education possesses four fundamental characteristics: theocentric, comprehensive and balanced, morality-oriented, and humanistic and universal. Islamic education confronts six major challenges encompassing ideology and thought, technology and information, the dichotomy of religious and general sciences, educator quality, welfare, and sociocultural value changes. Development strategies include integrative curriculum reform, modernization of learning methods, improvement of educator quality, strengthening of management, development of character education, and strategic cooperation. The integration of Islamic values with modern science through the Islamization of knowledge and integration-interconnection models becomes key to the relevance of Islamic education. The study concludes that Islamic education must adopt a moderate stance (wasathiyah) integrating classical heritage and modern advancement to produce graduates with deep religious knowledge, broad general knowledge, technological skills, and noble character.